WANGSALAN DENGAN UNSUR TUMBUHAN - Rini Esti Utami (Philosophica: Jurnal Bahasa, Sastra, dan Budaya, 2020)
ABSTRACTJavanese society is an agrarian society. In life they are very close to plants. One of the proofs of the Javanese culture that uses plants or parts of plants as the constituent elements is wangsalan. The research data was taken from the report on the collection of “Wangsalan in Javanese” (Utami, et al, 2016) and some wangsalan used on social media. Data analysis was performed using heuristic and hermeneutic reading techniques. After the data was analyzed, it was then presented with an informal method. This research describes the plants and plant elements present in wangsalan and the sound patterns of the answers or batangan of wangsalan with these plant elements. From the data analysis, it was found that the formers of wangsalan used plant elements with the mention of plants in general, namely the words wit-witan and wreksa. The names of plants used in wangsalan, namely aren, asem, gori, baligo, bayem, cubung, duren, ganyong, garut, gembili, jae, jagung, jalidrigung, jambu, jeram, jirak, kacang, kalapa and klapa, kawis, kelor, kemangi, kenthang, kluwih, kopi, krai, lombok, mlinjo, mrica, pakel, pandhan, pantun and pari, pring, pucang, pace, rotan, rumput, suruh, tanjung, tebu, terong, and uwi. The names of the parts of the plants used in wangsalan, namely babal, pentil gori, carang, kayu, godhong, rondhon, janur, sada, macung, puspa, puspita, sekar, and taru. The sound similarities between the questions and the answers or batangan in the wangsalan are the similarity of the last sound, the similarity of one or several sounds, the similarity of the front sound, the similarity of the middle sound, and the similarity of the whole sound (homonymy and polisemic relationship).